Religiosity as a Moderator in the Relationship between Lifestyle, Digital Promotion, and Impulsive Buying of Generation Z Muslims in Palopo City: A Sharia Economic Perspective - Saputri, Jesika; Sudirman; Idris Parakkasi; Syaharuddin; Sumarlin (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the influence of lifestyle and digital promotions on impulsive buying behavior among Generation Z Muslims in Palopo City, with religiosity as a moderating variable. This study uses a quantitative research type with an explanatory approach. Data were obtained by distributing questionnaires to 115 Generation Z Muslim respondents in Palopo City selected using a purposive sampling technique. Data analysis was conducted using SmartPLS software version 4.11.4 through the Partial Least Square (PLS) method to test validity, reliability, structural model, and research hypotheses. The results showed that each lifestyle and digital promotion variable had a positive and significant effect on impulsive buying. However, religiosity was not proven to moderate the influence of lifestyle or digital promotions on impulsive buying. This finding indicates a gap between the level of understanding of religiosity and consumption practices that still tend to be impulsive. Theoretically, this study strengthens the Stimulus–Organism–Response (SOR) study, while practically emphasizes the importance of financial literacy and digital literacy so that Generation Z can manage consumption behavior in accordance with the principles of simplicity in Islam. Kata Kunci: gaya hidup, promosi digital, impulsive buying, religiusitas, Generasi Z